Countering cyber sabotage : introducing consequence-driven, cyber-informed engineering (CCE) - Bochman, Andrew A.; Freeman, Sarah G. (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
Countering Cyber Sabotage: Introducing Consequence-Driven, Cyber-Informed Engineering (CCE) introduces a new methodology to help critical infrastructure owners, operators and their security practitioners make demonstrable improvements in securing their most important functions and processes. Current best practice approaches to cyber defense struggle to stop targeted attackers from creating potentially catastrophic results. From a national security perspective, it is not just the damage to the military, the economy, or essential critical infrastructure companies that is a concern. It is the cumulative, downstream effects from potential regional blackouts, military mission kills, transportation stoppages, water delivery or treatment issues, and so on. CCE is a validation that engineering first principles can be applied to the most important cybersecurity challenges and in so doing, protect organizations in ways current approaches do not. The most pressing threat is cyber-enabled sabotage, and CCE begins with the assumption that well-resourced, adaptive adversaries are already in and have been for some time, undetected and perhaps undetectable. Chapter 1 recaps the current and near-future states of digital technologies in critical infrastructure and the implications of our near-total dependence on them. Chapters 2 and 3 describe the origins of the methodology and set the stage for the more in-depth examination that follows. Chapter 4 describes how to prepare for an engagement, and chapters 5-8 address each of the four phases. The CCE phase chapters take the reader on a more granular walkthrough of the methodology with examples from the field, phase objectives, and the steps to take in each phase. Concluding chapter 9 covers training options and looks towards a future where these concepts are scaled more broadly.
OCLC-licensed vendor bibliographic record.
Keywords: Computer security -- United States; Computer crimes -- United States -- Prevention; Automation -- Security measures; Infrastructure (Economics) -- United States; National security -- United States; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; BUSINESS & ECONOMICS / Industrial Management